Office 365 : migrating and managing your business in the cloud - Katzer, Matthew A. (The expert's voice in Office 365, 2013)
Written for the IT professional and business owner, thisbook provides the business and technical insight necessary to migrate yourbusiness to the cloud using Microsoft Office 365. This is a practicallook at cloud migration and the use of different technologies to support thatmigration. Numerous examples of cloud migration with technical migrationdetails are included. Cloud technology is a tremendous opportunity for anorganization to reduce IT costs, and to improve productivity with increasedaccess, simpler administration and improved services. Those businessesthat embrace the advantages of the cloud will receive huge rewards inproductivity and lower total cost of ownership over those businesses thatchoose to ignore it. The challenge for those charged with implementing MicrosoftOffice 365 is to leverage these advantages with the minimal disruption of theirorganization. This book provides practical help in moving your businessto the Cloud and covers the planning, migration and the follow on management ofthe Office 365 Cloud services.